2009
DOI: 10.1182/blood-2009-03-201053
|View full text |Cite
|
Sign up to set email alerts
|

The role of complete response in multiple myeloma

Abstract: In multiple myeloma (MM), the impact of complete response (CR) could be shown only after introduction of high-dose therapy plus autologous stem cell transplantation (ASCT). In the context of ASCT, achieving CR (negative immunofixation and normal bone marrow) or at least very good partial response is associated with longer progression-free survival and in most studies longer survival. With novel agents, high CR rates are achieved and this prognostic impact of CR is being shown as well, both in relapsed and in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
148
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(159 citation statements)
references
References 89 publications
(22 reference statements)
6
148
0
5
Order By: Relevance
“…High dose melphalan and stem cell transplantation (SCT) has improved responses and lengthened survival (Harousseau et al, 2009). Advances in science have ushered in new classes of drugs including immunomodulatory agents (IMiDs) and proteasome inhibitors (PIs).…”
mentioning
confidence: 99%
“…High dose melphalan and stem cell transplantation (SCT) has improved responses and lengthened survival (Harousseau et al, 2009). Advances in science have ushered in new classes of drugs including immunomodulatory agents (IMiDs) and proteasome inhibitors (PIs).…”
mentioning
confidence: 99%
“…These response rates were similar to observed in previous studies with the VD regimen 9,10 but are higher than those obtained in studies with conventional chemotherapy. [4][5][6][7][8]13 Superiority of novel agents-based induction therapy both in terms of mobilization of stem cells and response rates to ASCT has been established. 1 Other studies showed that better pre-transplantation remission status implies better posttransplant CR rate.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that achieving CR is crucial for a long-lasting response and prolonged survival [7]. Patients who achieve immunofixation-negative CR after ASCT have significantly longer event-free survival and overall survival than those who remain in partial remission (PR) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional chemotherapy rarely achieves a major response, so high-dose chemotherapy with autologous stem cell transplantation (ASCT) is the standard treatment for MM patients under 65 years old [3,4]. After ASCT, a number of patients achieve prolonged progression-free survival [3][4][5][6][7][8]. Among several conditioning regimens, high-dose melphalan (HDM; 200 mg/m 2 ) is the recommended standard regimen for use before ASCT, because of its efficiency and acceptable toxicity [9].…”
Section: Introductionmentioning
confidence: 99%